Giant angiomatous choanal polyp originating from the middle turbinate: a case report - Perić, Aleksandar; Jovanovski, Aleksandar; Vukomanović Durdević, Biserka (ENT Updates, 2017)
Choanal polyps (CPs) can be defined as histologically benign, solitary, soft tissue lesions extending towards the junction between the nasal cavity and the nasopharynx through the choana. They usually originate from the maxillary sinus. In this report, we present an unusual case of a giant angiomatous CP arising from the inferior part of the middle turbinate that completely filled the nasopharynx. A 24-year-old man presented with five-year history of left-sided nasal obstruction, nasal discharge and mildto-moderate epistaxis. The diagnosis was supported by contrastenhanced computed tomography scan of the paranasal sinuses with angiography and confirmed by histopathological examination. The lesion was removed by combined endoscopic and transoral approach. In addition, we discuss the pathogenesis, clinical, radiological and pathological characteristics of angiomatous CPs, and their differential diagnosis.